Examining the State of Community Well-Being at the Intersection of Rurality and Agricultural Engagement in the Contiguous United States - Francois, Jean R.; Nelson, Katherine S. (My University, 2024)
As the 21st century progresses, rural residents across the United States have often found themselves in disadvantaged positions by many socio-economic measures compared to their urban counterparts. In addition, agriculture– once the emblem of rurality– shares a disputed relationship with the well-being of rural communities in social science literature. However, the literature specifically related to how community well-being (CWB) varies across both rurality and agricultural engagement is limited. This study addresses this gap in the body of knowledge. Using county-level data on socioeconomic conditions from the past decade, we examine how agricultural engagement is associated with community well-being in rural areas. We combine descriptive statistics and linear regression analysis with mapping techniques to identify and visualize patterns in the data. We show that CWB varies widely regardless of rural status and engagement in agriculture across the 3107 counties included in the study. However, the most disadvantaged communities are primarily located in rural places. Study findings also show that agricultural engagement is usually associated with somewhat improved, but not significantly different, CWB in rural areas. These findings indicate that the level of urbanicity/rurality might be the primary factor driving differences in CWB and that CWB in rural communities is generally similar regardless of local economies’ reliance on agriculture.
Keywords: Community well-being; Agricultural engagement; Intersection; Rurality; Socioeconomic conditions